2007
DOI: 10.1186/1471-2334-7-68
|View full text |Cite
|
Sign up to set email alerts
|

Using BOX-PCR to exclude a clonal outbreak of melioidosis

Abstract: Background: Although melioidosis in endemic regions is usually caused by a diverse range of Burkholderia pseudomallei strains, clonal outbreaks from contaminated potable water have been described. Furthermore B. pseudomallei is classified as a CDC Group B bioterrorism agent. Ribotyping, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) have been used to identify genetically related B. pseudomallei isolates, but they are time consuming and technically challenging for many laboratorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 23 publications
(27 reference statements)
2
52
0
1
Order By: Relevance
“…However, although BOX-PCR can provide results within 10 hours of a laboratory receiving the bacterial strains, it is less reproducible than PFGE, and a reliable comparison of BOX-PCR results between laboratories is not possible (27). We found variation in BOX-PCR results when we compared results from different PCR machines in our own laboratory and band-density differentials dependent on DNA template concentration (11).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, although BOX-PCR can provide results within 10 hours of a laboratory receiving the bacterial strains, it is less reproducible than PFGE, and a reliable comparison of BOX-PCR results between laboratories is not possible (27). We found variation in BOX-PCR results when we compared results from different PCR machines in our own laboratory and band-density differentials dependent on DNA template concentration (11).…”
Section: Discussionmentioning
confidence: 87%
“…We recently demonstrated that BOX-PCR can perform similarly to PFGE and MLST in typing B. pseudomallei, with the ability to usually discriminate between unrelated isolates, while also showing relatedness of epidemiologically linked isolates (11). However, although BOX-PCR can provide results within 10 hours of a laboratory receiving the bacterial strains, it is less reproducible than PFGE, and a reliable comparison of BOX-PCR results between laboratories is not possible (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to PFGE, the highly specific rep-PCR technique is an easy procedure, requiring little time for results, and is characterized by low labor costs [6][7][8] [8]. Recently, the BOX-PCR method was used for typing strains of different genera of Pseudomonas (Pseudomonas aeruginosa, Pseudomonas syringae, Pseudomonas putida and Pseudomonas fluorescens) [6,7,[9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…It has been applied in the classification and differentiation of strains of many Gram-positive and -negative bacteria including Bartonella (Rodriguez-Barrados et al, 1995), Bacillus subtilis (Pinna et al, 2001), B. sporothermodurans (Herman & Heyndrickx, 2000), E. coli (Leung et al, 2004;Panutdaporn et al, 2004;Silveira et al, 2003), Citrobacter diversus , Enterobacter aerogenes , Salmonella (Chmielewski et al, 2002;Kerouanton et al, 1996;Millemann et al, 1996;Rasschaert et al, 2005), Vibrio cholerae (Colombo et al, 1997;Rivera et al, 1995), Pseudomonas corrugata (Achouak et al, 2000), Vibrio parahaemolyticus (Khan et al, 2002;Son et al, 1998), Pseudomonas syringae-Pseudomonas viridiflava group (Marques et al, 2008), Aeromonas spp. (Taco et al, 2005), Xanthomonas (Rademaker et al, 2000), Rhizobium meliloti (De Bruijn, 1992;Niemann et al, 1997), Pandoraea apista (Atkinson et al, 2006), methicillin-resistant S. aureus (Van Belkum et al, 1992), S. pneumoniae , A. baumanii (Dijkshoorn et al, 1996), Burkholderia cepacia , B. pseudomallei (Currie et al, 2007), L. pneumophilia (Georghiou et al, 1994), Helicobacter pylori (Kwon et al, 1998), N. gonorrhoeae (Poh et al, 1996), N. meningitidis (Woods et al, 1996), Enterococcus spp. (Svec et al, 2005), Paenibacillus larvae subsp.…”
Section: Rep-pcrmentioning
confidence: 99%